Global sukuk market: analysis of the current state and development features - Alexandra P. Chigrinskaya (RUDN Journal of Economics)
The aim of this research is to study the current state and development features of the global sukuk market in the context of national markets included in its composition. The largest sukuk markets located in Malaysia, Indonesia, Iran, Saudi Arabia, United Arab Emirates, Turkey and Qatar were identified in order to delimit the research area for a more in-depth analysis. The markets of the specified countries were examined from the perspective of the sukuk terms, the currency of the denomination, types of issuers (both by industry and by sector (sovereign and corporate)), trading platforms they are circulated on. The analysis allowed us to conclude that according to different criteria, a list of leaders and outsiders is distinguished and these lists do not coincide. At the same time, there were countries whose situation with sukuk was radically different from the main group of countries during the analysis for each criterion. The information agency Cbonds was the main source of countries statistical information for calculations.